Heritage Preservation of the Pulau Sawah Temple Complex in Dharmasraya Regency, Indonesia - Merlina Agustina Orllanda; Herwandi Herwandi; Nopriyasman Nopriyasman (Diponegoro University, 2025)
The study focused on the preservation of the Pulau Sawah Temple complex under the management of Batusangkar Historical and Archaeological Heritage Conservation Agency (SPSP) Batusangkar to the Cultural Preservation Centre (BPK) III Region West Sumatra. The temple site had previously received inadequate attention, both from the community and the local government, even though it marked the heritage of the Buddhist Malay Kingdom. The situation improved when the SPSP was established and began operations, leading to increased attention and conservation efforts for the Pulau Sawah temple complex through various stages. Through primary and secondary source research, the study found that the conservation of the Pulau Sawah temple complex has involved numerous stakeholders. Various local stakeholders, supported by the Batusangkar SPSP as the precursor to the BPK III, have played a crucial role in the preservation process. Preservation efforts are not limited to collection management but are also supported by the management of the organisational structure of the institution responsible for the site complex. Therefore, the preservation of the temple structures on Pulau Sawah, which, when examined closely, can evoke the identity of Dharmasraya, is of great value and should be passed on to future generations.